Implementasi Sistem Penjaminan Mutu Internal (Spmi) Dalam Meningkatkan Mutu Layanan Pendidikan : Implementation of the Internal Quality Assurance System (SPMI) in Improving the Quality of Education Services - Warta, Waska; Sulastriningsih, Kursih; Umronih, Dewi (Technomedia Journal, 2024)
Improving the quality of education, it is important to build a culture of quality in schools through the implementation of the Internal Quality Assurance System (SPMI) as ordered by the government. This research focuses on the implementation of SPMI at SMP Lab School FIP UMJ Cirendeu Ciputat Tangerang Banten. The aim is to analyze how the implementation of SPMI improves the quality of educational services at the school. Data is collected through observation, interviews and documentation, then analyzed to draw conclusions. The research results show several aspects: 1) quality mapping instruments that are not fully in accordance with the quality indicators of the 8 National Education Standards (SNP), 2) quality fulfillment targets that are not yet optimal, 3) fulfillment of the 8 SNP fulfillment targets, 4) improving the quality of the learning process and school management, 5) improving the quality of learning outcomes, establishing a quality culture, and continuing quality improvement. Thus, the implementation of SPMI at SMP Lab School FIP UMJ Cirendeu Ciputat Tangerang Banten has a positive impact in improving the quality of educational services.